Why are we still using antibiotic prophylaxis in elective laparoscopic cholecystectomy for the low-risk groups? a review of literature - Shyam, Devajit Chowlek; Shyam, Ranjit Chowlek; Khongwar, Donkupar; Tongper, Dathiadiam (International Surgery Journal, 2021)
Gallstone disease is one of the most common gastrointestinal conditions requiring surgery and more than 90% of cholecystectomies are done laparoscopically. The major complications of laparoscopic cholecystectomy are major bleeding, Bile duct injury, and wound infection or surgical site infection. The incidence of Surgical site infection in laparoscopic cholecystectomy (0.4-1.13%) is significantly low compared to open cholecystectomy (3-47%) and the probable reasons are the smaller incision and the use of trocar along with almost nil to minimal wound contamination as compared to open cholecystectomy. Port site infection is a type of surgical site infection (1.8%) and the Umbilical port site is the most common site followed by the epigastric port site. In spite of the low-risk of surgical site infection, many surgeons still practice antibiotic prophylaxis in elective laparoscopic cholecystectomy for low-risk patients. Antibiotic prophylaxis is a debatable topic in the low-risk group undergoing elective laparoscopic cholecystectomy.Meticulous preoperative skin preparation is one of the established local factors to prevent the occurrence of SSI.